AN OVERVIEW OF ACTIVE SMOKERS’ PERCEPTIONS OF THE POLICY OF INCLUSION OF PICTORIAL WARNINGS OF THE DANGERS OF SMOKING ONCIGARETTE PACKS IN PONDOK GEDE SUB-DISTRICT, BEKASI CITY - Hermansach, Rendra; Bachtiar, Adang (UI Scholars Hub, 2021)
The prevalence of smoking in Indonesia is so high in all walks of life that the government has made several policies to control it. One of them is the inclusion of health warnings and health information on tobacco product packaging which aims to prevent novice smokers from starting smoking, as well as guaranteeing the public's right to clear, correct and honest information, as well as choosing based on clearer (visual) information that they understand (informed decision). The purpose of this study was to determine the extent of active smokers' perceptions of pictorial warnings of the dangers of smoking on cigarette packs. Subjects and Methods: This study uses a qualitative approach and the Extended Parallel Process Model (EPPM) method. The research subjects consisted of active smokers who were found in Pondok Gede District, Bekasi City. Data collection techniques in this study were in-depth interviews. The research instrument used was the researcher himself who was directly involved in the research. Then the technique of checking the validity of the data uses source triangulation. Results: The results showed that the informants' perceptions of the pictorial warnings of the dangers of smoking on cigarette packs varied quite a lot. Not all informants feel afraid and horrified by the scary pictures on cigarette packs. These results affect their beliefs to be able to reduce or quit smoking. Those who feel afraid and spooky of the pictures on cigarette packs have more confidence to be able to stop smoking than those who don't feel scared or spooky. Conclusion: Based on the results of the analysis it can be concluded that the pictorial warnings on cigarette packs has not been able to reduce the desire to quit smoking among informants.